Semantic Frames of ‘Rabb’ in the Quran (A Cognitive Linguistics Approach Validated through Hadith Triangulation and Islamic Epistemological Framework) - Slamet Riyadi; Muhammad Thalib (WARAQAT : Jurnal Ilmu-Ilmu Keislaman, 2025)
This study investigates the semantic frames and conceptual constructions of the term رَبّ (rabb/Lord) in the Quran through a cognitive linguistic approach, specifically Frame Semantics (Fillmore, 1982) and Conceptual Metaphor Theory (Lakoff & Johnson, 1980). While the concept of rububiyyah has been extensively studied theologically, systematic semantic-cognitive analysis of this fundamental concept remains limited. Using a mixed-methods design, we analyzed 25 representative verses from the Quranic Arabic Corpus through a five-stage frame identification protocol. Six primary semantic frames were identified: Divine_Creation, Divine_Provision, Divine_Guidance, Divine_Sovereignty, Divine_Nurturing, and Divine_Mercy, with significant differences in frame frequency between Makki and Madani revelations (χ²=18.47, p<0.01). Three dominant conceptual metaphors structure the concept of Rabb: RUBUBIYYAH IS NURTURING, RUBUBIYYAH IS SOVEREIGNTY, and DIVINE PROVISION IS DESCENDING. Findings were triangulated with classical tafsir (Ibn Kathir, al-Tabari), five sahih hadiths (Bukhari, Muslim), and Salafi scholarship (Ibn Uthaymin, Ibn Baz), demonstrating that cognitive linguistic methods can enhance semantic understanding of the Quran without compromising theological authenticity.